The Role of Self-Compassion as a Moderator between Physical Appearance Comparison and Social Appearance Anxiety in Emerging Adult Women - Nasution, Nur Aisyah Rahmani; Khostarina, Tina; Zahra, Nikita (MOTIVA: JURNAL PSIKOLOGI, 2025)
Physical apprearance is an important aspect and people generally assess their appearance by comparing themselves with other. Comparing oneself to others can increase the tendency to experience anxiety, especially when one’s appearance is perceived as less attractive than the comparison target or ideal standards in society. This study aimed to observe the roles of self-compassion moderating the relationship between physical appearance comparison and social appearance anxiety in women in the phase of emerging adult. The hypothesis proposed is that self-compassion is able to moderate the relationship between physical appearance comparison and social appearance anxiety. There were 404 women aged in the range of 18-25 years old involved as the subject of this research and the selection of the research subject was conducted using the purposive sampling technique. The instrument used in this research was Self-Compassion Scale-Short Form (SCS-SF), Physical Appearance Comparison Scale-Revised (PACS-R), and Social Appearance Anxiety Scale (SAAS). Data analysis was conducted using the Moderated Regression Analysis (MRA) by means of JASP program. This research showed that self-compassion can act as the moderator of the relationship between physical appearance comparison and social appearance anxiety in emerging adult women. Self-compassion in  emerging adult women can decrease the negative effect of physical appearance comparison, so that anxiety related to appearance that is felt when interacting in social environment can be minimized.